Understanding the role of distinguishability in multiphoton interference from a quantum operations perspective (2022)
In this work we present an alternative view of multiphotonic interference from a quantum operations perspective. The development of such alternative begins with considering the two-photon interferometer, and analyzing the evolution of the quantum state from an indistinguishable particles perspective. Later, the behaviour of more than two photons in a beam splitter is analyzed using group theory and information theory.